Captain Cook : master of the seas - McLynn, Frank (Yale University Press, 2012)
Profiles the famous navigator, addresses the common colonialist misconceptions about the explorer and his death, and re-creates the voyages that took him from his native England to the outer reaches of the Pacific Ocean.